ADMISSION AND READMISSION IN HEART FAILURE, PREDICTORS OF READMISSION, AN EXPERIENCE AT AYUB TEACHING HOSPITAL ABBOTTABAD - Awan, Muhammad Saleem; Iqbal, Muhammad Khaleel; Matiullah Khan; Naveed, Danish; Afsar, Rukhshanda; Jalil, Shaista (Journal of Ayub Medical College Abbottabad, 2024)
Background: Heart failure is a long-term health condition that is characterized by multiple re-admissions throughout the patient’s life. The economic burden and the impairment of quality of life are too prominent in patients with heart failure. The aim of the study was to determine re-admission rate and predictors of re-admission in patients with heart failure at Ayub Teaching hospital Abbottabad. Methods: A data of 350 patients with heart failure who were admitted & readmitted to the coronary care unit with heart failure were included in this study. Data was collected to determine the common factors that may dictate their readmission to hospital. Results: Over all re-admission rate was 58.28 %(n=204) for the patients in our study cohort. Regarding readmission rates within a 90-days period, 41.7% (n=146) of the sample had no readmission events, 35.1% (n=123) had one readmission, and 23.1% (n=81) experienced two or more readmissions. In terms of comorbid conditions, 36.9% (n=129) of the patients had a diagnosis of diabetes mellitus, while 57.7% (n=202) had hypertension. There was a statistically significant association between readmission within 90 days following first hospitalization for heart failure and diabetes mellitus, Increased Heart Rate, Nephropathy and an increased Neutrophil: Lymphocyte ratio (p<0.05). Conclusion: Diabetes mellitus, elevated heart rate, the presence of nephropathy, and an increased neutrophil-lymphocyte ratio were found to be independent predictors of subsequent heart failure readmission. These risk factors could potentially serve as simple indicators for forecasting the likelihood of heart failure readmission following patient discharge.